Marketing Survey of Acid Lime and Hill Lemon in Nepal - Dhakal, DD; Tripathi, KM; Bhattarai, S (Journal of the Institute of Agriculture and Animal Science, 2005)
A market survey was undertaken visiting 14 major markets of the country during 2001/03 to assess the marketing system, demand and supply situation and price behavior of acid lime and hill lemon in Nepal. Different levels of market intermediaries involved in lime and hill lemon marketing were selected for survey and group discussion. A standard semi structured interview schedule was used to gather the information and daily transaction of lime was recorded in Kalimati wholesale market for one year. The total annual consumption of lime at 14 major markets of Nepal was over 2327 mt. of which, 85% was consumed in Kathmandu only. The volume of sale was higher during main season of production in all markets except Nepalgunj, Bhairahawa and Krishnanagar, where the volume of sale was higher in off-season. Over 90 percent of total lime marketed in Nepal was imported from India. In Kalimati wholesale market, the domestic lime contributed only 5.5% to total supply in the season and the rest was supplied from India. However, the share of Nepalese lime in other 13 major markets, outside the Kathmandu valley, was 32%. The total volume of import was 2108 t. valued at Rs. 50.4 millions. In contrast to lime, lemon was not imported from India. The demand of lime was higher during off-season from January to August and lower during the main season of production, i.e. September to December. The wholesale and retail prices of lime and hill lemon showed temporal and spatial variation. The average wholesale price of two years (2001-2003) in Kalimati market was Rs. 1.2 to 2.6 and retail Rs. 1.5 to 3.05/fruit, whereas in 13 major markets the wholesale price varied from Rs. 0.64/fruit in September to Rs. 0.95 in April. Average retail price was the lowest in August (Rs. 1.4/fruit) and the highest in April (Rs. 1.93/fruit). Similarly, the average wholesale price of hill lemon varied from Rs. 1.6/fruit in October to Rs. 6.0/fruit in April and the average retail price was the lowest in October (Rs. 2.4/fruit) and the highest in April (Rs. 7.0/fruit). The prices of lime and hill lemon were the lowest during the season of production and the highest during off-season, i.e. summer months. Different types of traders as suppliers, wholesalers, retailers, doke, four-wheelers, collectors and commission agents were involved in the marketing of lime and hill lemon. There were four different channels involved in the marketing of lime and hill lemon. Shares of those channels in business varied with markets. The marketing through commission agent (6%) was not common, whereas the collectors were significant (57%) in marketing. The common uses of lime and hill lemon were as fresh green salad, juice and processed products such as juice, squash, chuk, and pickle. The post-harvest loss during marketing was up to 20 -25% due to poor management of fruits. Development of technology for the higher productivity, off-season production, post harvesting handling and processing of fruits, and strengthening market facilities including cold storage are suggested to reap the tremendous internal market opportunities and substitute the imports. Key words: Acid lime, hill lemon, marketing J. Inst. Agric. Anim. Sci. 26:107-116 (2005)